Religion and secular modernity in Russian Christianity, Judaism, and atheism - Siljak, Ana (NIU series in Slavic, East European, and Eurasian studies, 2024)
"The contributors to this collection of essays investigate the multiple ways in which Christianity, Judaism, and atheism navigated the intersection of religion and secular modernity in Russian and Soviet history and in the post-Soviet world"--